Toward confidential distributed medical emergency system and security service - Hameed, Shihab A.; Yuchoch, Habib; Al-Khateeb, Wajdi Fawzi Mohammed (2010)
Medical Emergency System in the future would be a worldwide system which leads to private data that will be transmitted over network. Privacy is a strong requirement for systems dealing with personal medical data. A major factor of in the success of web service systems and many new software products are being designed to have a high level of trust. Traditionally trust was mainly associated with the security of the system to make sure that the user is authorized and not allowing unauthorized access. This paper proposes security components for distributed Medical Emergency System. It present the way of making security components for a distributed Medical Emergency System application and provides a secure connection among local server. Moreover, handshaking and user authentication between two parties are also presented. Security services is designed and applied for some purpose especially for Medical Emergency System. The security services are important and beneficial for healthcare system. This security was traditionally achieved by the use of encryption of data and other security techniques and password.